Tongue Gestures for Hands-Free Interaction in Head Worn Displays - Gemicioglu, Tan; Winters, R. Michael; Wang, Yu-Te; Tashev, Ivan (26th Annual International Symposium on Wearable Computers, 2022)
Head worn displays are often used in situations where users' hands may be occupied or otherwise unusable due to permanent or situational movement impairments. Hands-free interaction methods like voice recognition and gaze tracking allow accessible interaction with reduced limitations for user ability and environment. Tongue gestures offer an alternative method of private, hands-free and accessible interaction. However, past tongue gesture interfaces come in intrusive or otherwise inconvenient form factors preventing their implementation in head worn displays. We present a multimodal tongue gesture interface using existing commercial headsets and sensors only located in the upper face. We consider design factors for choosing robust and usable tongue gestures, introduce eight gestures based on the criteria and discuss early work towards tongue gesture recognition with the system.